Combining targeted and systematic prostate biopsy improves prostate cancer detection and correlation with the whole mount histopathology in biopsy naïve and previous negative biopsy patients - Mischinger, Johannes; Schöllnast, Helmut; Zurl, Hanna; Geyer, Mark; Fischereder, Katja; Adelsmayr, Gabriel; Igrec, Jasminka; Fritz, Gerald; Merdzo-Hörmann, Martina; Elstner, Jörg; Schmid, Johannes; Triebl, Alfred; et al. (Frontiers in Surgery, 2022)
Objective: Guidelines for previous negative biopsy (PNB) cohorts with a suspicion of prostate cancer (PCa) after positive multiparametric (mp) magnetic-resonance-imaging (MRI) often favour the fusion-guided targeted prostate-biopsy (TB) only approach for Prostate Imaging-Reporting and Data System (PI-RADS) ≥3 lesions. However, recommendations lack direct biopsy performance comparison within biopsy naïve (BN) versus PNB patients and its prognostication of the whole mount pathology report (WMPR), respectively. We suppose, that the combination of TB and concomitant TRUS-systematic biopsy (SB) improves the PCa detection rate of PI-RADS 2, 3, 4 or 5 lesions and the International Society of Urological Pathology (ISUP)-grade predictability of the WMPR in BN- and PNB patients. Methods: Patients with suspicious mpMRI, elevated prostate-specific-antigen and/or abnormal digital rectal examination were included. All PI-RADS reports were intramurally reviewed for biopsy planning. We compared the PI-RADS score substratified TB, SB or combined approach (TB&SB) associated BN- and PNB-PCa detection rate. Furthermore, we assessed the ISUP-grade variability between biopsy cores and the WMPR. Results: According to BN (n=499) vs. PNB (n=314) patients, clinically significant (cs) PCa was detected more frequently by the TB&SB approach (62 vs. 43%) than with the TB (54 vs. 34%) or SB (57 vs. 34%) (all p<0.0001) alone. Furthermore, we observed that the TB&SB strategy detects a significantly higher number of csPCas within PI-RADS 3, 4 or 5 reports, both in BN and PNB men. In contrast, applied biopsy techniques were equally effective to detect csPCa within PI-RADS 2 lesions. In case of csPCa diagnosis the TB approach was more often false-negative in PNB patients (BN 11% vs. PNB 19%; p=0.02). The TB&SB technique showed in general significantly less upgrading, whereas a higher agreement was only observed for the total and BN patient cohort. Conclusion: Despite csPCa is more frequently found in BN patients, the TB&SB method always detected a significantly higher number of csPCas within PI-RADS 3, 4 or 5 reports of our BN and PNB group. The TB&SB strategy predicts the ISUP-grade best in the total and BN cohort and in general shows the lowest upgrading rates, emphasizing its value not only in BN but also PNB patients.